Outcomes Following the Treatment of Talar Osteochondral Lesions with BioCartilage and Bone Marrow Aspirate Concentrate Mixture. Issue 3 (14th September 2018) - Fansa, Ashraf; Drakos, Mark; Cabe, Taylor; Fabricant, Peter
Category: Arthroscopy Introduction/Purpose: With reported incidence rates ranging from 40% to 70% post ankle sprains and fractures, osteochondral lesions of the talus (OLT) are not uncommon. However, management of such defects remains challenging. Microfracturing is considered the standard treatment for symptomatic OLTs.Larger lesions however typically require more invasive restorative procedures such as autologous osteochondral transplantation. Microfracture results are variable due to the fact that the resulting reparative fibrocartilage is weaker and biomechanically inferior to native hyaline cartilage. In this study, we examine the functional and radiological outcomes following use of a new arthroscopic technique utilizing a mixture of micronized allograft cartilage matrix (BioCartilage) (Arthrex, Naples, FL) soaked in Bone Marrow Aspirate Concentrate (BMAC) to fill OLTs. Methods: Eighty-six consecutive patients treated for OLT using arthroscopic debridement and BioCartilage matrix soaked in BMAC were identified. All patients were treated by a single fellowship-trained sports medicine and foot and ankle surgeon. Functional outcomes were assessed using the Foot and Ankle Outcome Score (FAOS) and Patient-Reported Outcomes Measurement Information System (PROMIS). This information was obtained from a prospective registry at the authors' institution. Wilcoxon signed rank tests were used to determine statistical significance between pre and postoperative clinical scores. Additionally, an attending radiologist assessed the reparative cartilage morphology on postoperative MRI scans. This was evaluated and scored using a modified magnetic resonance observation of cartilage tissue (MOCART) scoring system. Results: Thirty-one patients (19 Females; 12 Males) with a mean age of 37.8 years (Range 15–54) had a minimum follow-up duration of 12 months and were thus included in this review. Mean follow-up duration was 15.8 months (Range 12 –25.7). The mean patient BMI was 27.4 (Range 19.6 – 39.4), while the average osteochondral lesion size was 85.9 mm2 (Range 35 – 220). The Physical Function domain of the PROMIS score, demonstrated statistically significant change, improving from 40.63 ±8.31 to 48.31 ±10.07 (p=0.02). The Pain Intensity domain also improved significantly from 49.06 ±9.32 to 42.14 ±9.38 (p=0.03). The Pain Interference domain and FAOS scores did improve but not reaching statistical significance. The mean MRI MOCART score was 69 ±13.34 with 13.3 months average follow-up duration. Conclusion: Achieving the longest duration possible of symptom-free functioning postoperatively is the main goal of any cartilage repair procedure. Augmentation of an articular lesion's infill with BioCartilage and BMAC may help enhance the biomechanical properties of the reparative fibrocartilage construct and its longevity. Our initial findings demonstrate favorable patient-reported outcomes. Moreover, postoperative MRIs demonstrate the majority of the lesions showed either complete or hypertrophic infill, complete or hypertrophic integration, homogenous repair tissue, and isointense signals. Long-term studies prospectively assessing the effectiveness of this technique in maintaining pain-free-function of the ankle joint are warranted.